2018
DOI: 10.1259/bjr.20180004
|View full text |Cite
|
Sign up to set email alerts
|

Proton relative biological effectiveness (RBE): a multiscale problem

Abstract: Proton radiotherapy is undergoing rapid expansion both within the UK and internationally, but significant challenges still need to be overcome if maximum benefit is to be realised from this technique. One major limitation is the persistent uncertainty in proton relative biological effectiveness (RBE). While RBE values are needed to link proton radiotherapy to our existing experience with photon radiotherapy, RBE remains poorly understood and is typically incorporated as a constant dose scaling factor of 1.1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…While the evidence supporting variable proton RBE due to increased LET in in-vitro and animal studies is solid, [5][6][7]69 the first reports of statistically significant data in human subjects (although using subclinical endpoints) were published only recently. A study in 34 ependymoma patients found a correlation between incidence of post-treatment image changes in magnetic resonance and both dose and LET.…”
Section: Introductionmentioning
confidence: 99%
“…While the evidence supporting variable proton RBE due to increased LET in in-vitro and animal studies is solid, [5][6][7]69 the first reports of statistically significant data in human subjects (although using subclinical endpoints) were published only recently. A study in 34 ependymoma patients found a correlation between incidence of post-treatment image changes in magnetic resonance and both dose and LET.…”
Section: Introductionmentioning
confidence: 99%
“…PBT is increasingly used in clinical settings worldwide. However, there are also increasing concerns about its biological uncertainty [6,7,8,18,19,20,21]. Heavy ions, such as carbon ions, consider RBE variations in treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…The design of base-of-skull IMPT plans which are biologically robust, physically robust and clearly superior to VMAT in terms of OAR sparing, is non-trivial. Worldwide, considerable effort is being applied to the development of new methods for (i) robust IMPT optimization based on physical and biological parameters and (ii) IMPT robustness analyses [48]. ‘Worst case’ uncertainty scenarios (as employed in the commercial TPS we used) are sometimes criticized for being overly conservative [48]: stochastic or probabilistic approaches form an active area of research and a viable alternative [12].…”
Section: Discussionmentioning
confidence: 99%
“…Further work however could usefully investigate the accuracy of the analytical LET d script provided by Varian under a range of clinical circumstances. The suitability, or otherwise, of averaged LET as a surrogate for biological effect also warrants further investigation [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation